Disciplinary Punishment in the Public Service: A Comparative Study - Rajab Salman , Researcher. Walid (Basra studies journal, 2025)
Disciplinary sanctions in public service are primarily intended to deter employees and motivate them to perform their duties fully and correctly, in accordance with the applicable legal rules. These sanctions constitute a tool used by the administration to safeguard the public interest and ensure the proper execution of its directives. In this sense, disciplinary punishment is a means rather than an end in itself. Disciplinary measures are not limited to the notion of punishment; their broader purpose is to reform and enhance the efficiency of public employees. When an employee realizes that any negligence in performing his duties may lead to a penalty imposed by the competent authorities, this awareness contributes to discipline, accountability, and professional improvement. Given the wide discretionary authority granted to public administration in imposing disciplinary penalties on violating or delinquent employees, such penalties may sometimes be flawed, unlawful, or affected by procedural or substantive defects that undermine their validity. They may also contravene the principle of legality, making them subject to challenge through administrative grievance mechanisms.